Confucianism and Tokugawa culture (Princeton University Press, 1984)
Introduction : Neo-Confucianism and Tokugawa discourse / Peter Nosco -- Neo-Confucianism and the formation of early Tokugawa ideology : Contours of a Problem / Herman Ooms -- Tokugawa Confucian historiography : the Hayashi, early Mito School, and Arai Hakuseki / Kate Wildman Nadkai -- Tokugawa peace and popular religion : Suzuki Shosan, Kakugyo Tobutsu, and Jikigyo Miroku / Royall Tyler -- Characteristic responses to Confucianism in Tokugawa literature / Donald Keene -- Nature and artifice in the writings of Ogyu Soria (1666-1728) / Samuel Hideo Yamashita -- Maxuho Zanko (1655-1742) : a Shinto popularizer between nativism and national learning / Peter Nosco -- Jiun Soja (1718-1804) : a response to Confucianism within the context of Buddhist reform / Paul B. Watt -- Neo-Confucian thinkers in nineteenth-century Japan; Takehiko Okada -- Nakae Chomin and Confucianism; Sannosuke Matsumoto